1998
DOI: 10.1002/(sici)1521-3951(199805)207:1<233::aid-pssb233>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of the Electrical Resistivity of a-FeZr Alloys

Abstract: The temperature dependence of electrical resistivity of a-Fe 100±x Zr x alloys (x = 8.5 and 9.5) is measured in the temperature range 5 to 300 K. Our observations indicate some correlations between the magnetic and electrical resistivity behavior near the transition region. The resistivity data have been analyzed in the light of both magnetic and nonmagnetic scattering models to quantify the contributions from these scattering processes. From the quantitative analysis it is found that the magnetic contribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(27 reference statements)
1
1
0
Order By: Relevance
“…For example, Fe 90 Zr 10 has almost constant resistivity throughout the temperature interval 10-300 K, while Fe 85 Zr 15 varies significantly within the same temperature range. Similar behavior has been reported in the literature [17][18][19]. The changes in resistivity are in strong contrast to the spectroscopic measurements which reveal only small changes when changing the composition; see figures 5, 7 and 8.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For example, Fe 90 Zr 10 has almost constant resistivity throughout the temperature interval 10-300 K, while Fe 85 Zr 15 varies significantly within the same temperature range. Similar behavior has been reported in the literature [17][18][19]. The changes in resistivity are in strong contrast to the spectroscopic measurements which reveal only small changes when changing the composition; see figures 5, 7 and 8.…”
Section: Discussionsupporting
confidence: 89%
“…In previous work on the resistivity in amorphous metallic glasses, it was concluded that a combination of magnetic and non-magnetic scattering is necessary for the interpretation of the experimental data [17]. Composition variations, such as those investigated here, influence the local atomic structure of the amorphous Fe 100−x Zr x alloys.…”
Section: Discussionmentioning
confidence: 71%